Development of a Complex Vulnerability Index for Fishing Shelters—The Case of Cyprus - Vasiliki I. Chalastani; Andreas Pantelidis; Elissavet Feloni; Andreas Papadimitriou; Christina N. Tsaimou; Olympia Nisiforou; Vasiliki K. Tsoukala (Journal of Marine Science and Engineering, 2023)
Small fishing harbours substantially contribute to coastal economies as they support not only fishing but also tourism activities. They are located at the land–sea interface and are considered vulnerable infrastructure affected by the increased human activities but also by the impacts of climate change, including rising sea levels and extreme weather events. In this paper, the 16 existing fishing shelters of Cyprus are used as a case study to develop a complex vulnerability index for assessing the shelters’ vulnerability. The index incorporates physical, environmental, technical and socioeconomic variables, which are quantified and scored to denote the current state of vulnerability. The results are validated through on-site visits, questionnaires answered by local fishermen and targeted interviews with representatives of the port authorities. Furthermore, climate change projections are taken into account for the physical variables to evaluate the impact of climate change on vulnerability changes. The study highlights the complex interactions between a variety of factors characterising the fishing shelters and driving vulnerability. The proposed index can assist decisionmakers with prioritising interventions, allocating funding and designing adaptation pathways that reduce the shelters’ vulnerability while increasing their resilience.